2012
DOI: 10.17161/foec.v44i6.6685
|View full text |Cite
|
Sign up to set email alerts
|

Supporting Paraeducators through a Collaborative Classroom Support Plan

Abstract: Ms. Simmons was eager to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Granted, some paraprofessionals may not appear to care about their role in the classroom, but as Abbott and Sanders (2013) noted, they may be disengaged because they do not fully understand their purpose in a music setting. As has also been found in previous research, paraprofessionals may not know what their role in the music classroom should be (Bernstorf, 2001; Giangreco, 2013), and so music teachers could serve their colleagues by assuming the lead in respectful communication (Brown & Stanton-Chapman, 2017; Capizzi & Da Fonte, 2012; Darrow, 2010).…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…Granted, some paraprofessionals may not appear to care about their role in the classroom, but as Abbott and Sanders (2013) noted, they may be disengaged because they do not fully understand their purpose in a music setting. As has also been found in previous research, paraprofessionals may not know what their role in the music classroom should be (Bernstorf, 2001; Giangreco, 2013), and so music teachers could serve their colleagues by assuming the lead in respectful communication (Brown & Stanton-Chapman, 2017; Capizzi & Da Fonte, 2012; Darrow, 2010).…”
Section: Discussionmentioning
confidence: 54%
“…We found that almost no one provided training outside music classes. Although researchers have reported that discussing teaching style and expectations with paraprofessionals can be highly productive (Brown & Stanton-Chapman, 2017; Capizzi & Da Fonte, 2012; Darrow, 2010), participants in our study cited lack of time as the greatest deterrent. Paraprofessionals are often paid by the hour during the regular school day; therefore, meeting before or after school could represent work without remuneration.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations